The Influence of Learning Facilities, Learning Motivation and Learning Methods on Student Learning Achievement at Darul Ulum Waru Sidoarjo Junior High School - Salwa Sabrina; Siti Kholidatur Rodiyah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Student learning achievement is a benchmark for the quality of education in Indonesia. Various internal and external factors influence the current decline in the quality of education in Indonesia. The purpose of this study is to analyze the influence of learning facilities, learning motivation, and learning methods on student learning achievement at Darul Ulum Waru Middle School, Sidoarjo. A quantitative explanatory survey was applied in this study with 255 respondents at Darul Ulum Waru Middle School, Sidoarjo. The 255 students who constitute the population were also used as the research sample. Primary and secondary data are the sources of this research obtained through the distribution of questionnaires in the form of Google Forms, while secondary data were obtained from written sources, such as previous surveys. This study collected data through interviews with the Deputy Curriculum at Darul Ulum Waru Middle School, Sidoarjo, and by reviewing documents related to this study, such as lists of academic and non-academic achievements. The data obtained will be tested using the multiple linear regression method. The results of the study illustrate that three factors contribute to student achievement at Darul Ulum Waru Sidoarjo Middle School: learning motivation has a significant effect on student achievement, learning facilities do not have a significant effect on student achievement, and learning methods have a significant effect on student achievement.